Synthesis and properties of 1,2,4-triazole-3-thiol derivatives with a thiadiazole moiety - Fedotov, S. O.; Hotsulia, A. S.; Федотов, Сергій Олегович; Гоцуля, Андрій Сергійович (My University, 2021)
Materials and methods. Target esters were obtained in two ways. The first method was the alkylation of the starting 4-phenyl-5-(((5-(phenylamino)-1,3,4-thiadiazol-2-yl)thio)methyl)-1,2,4-triazole-3-thiol with methyl , ethyl, n-propyl, isopropyl, tert-butyl, n-pentyl, iso-pentyl ester of 2-chloroetanoic acid in propan-2-ol with an equivalent amount of sodium hydroxide.